(untitled) (Modern information system and technologies, 2018)
In paper considered, models of quasi-fractal dielectric resonator antennas (DRA) based on a cube and truncated pyramid. Ansoft HFSS package used for their synthesis. For the purpose of evaluation influence of antenna geometry on its space-frequency characteristics, variants for DRA composition defined which differ in location of elements and depth of their overlap. Analysis of the results performed based on comparison frequency response, radiation pattern and standing wave ratio.